The Effect of Collaborative Strategic Reading (CSR) and Critical Reading on Students’ Reading Comprehension - Eneng Liah Khoiriyah; Eka Dewi Fithrotunnisa; Dede Imtihanudin (ELT-Lectura, 2023)
Abstract: Eka Dewi Fithrotunnisa, Eneng Liah Khoiriyah, Dede Imtihanudin., The Collaborative Strategic Reading (CSR) and Critical Reading on Students’ Reading Comprehension (A Quasi-experimental Research in the Second Grade Students of Private Junior High School; MTs Muhammadiyah I Ciputat, SMP Darussalam and SMP Islamiyah Ciputat). This research was aimed at proving empirically the effect of collaborative strategic reading (CSR) and critical reading on students’ reading comprehension at the second grade of Private Junior High School in Ciputat. The quantitative method with quasi-experimental design was undertaken to analyze the effect of CSR and critical reading on students’ reading comprehension. The population in this research was all students of three of Private Junior High School in Ciputat in academic year 2022/2023 consisted of 8 classes in which each class had about 20-25 students. Because of time limitation, the target population was grade 8 students. In MTs Muhammadiyah 1 Ciputat is only consisted of 3 classes, SMP Darussalam Ciputat is consisted of 3 classes and SMP Islamiyah is consisted 2 classes. Meanwhile, the samples of this research were two classes of each school at second grade students; one class as experimental class comprised of 20 students, and the other as control class comprised of 20 students as well. These samples were determined by using intake sampling technique because the samples taken were the classes that already existed in that school. It aimed to not interfere the teaching and learning process and procedures that had been established in that school. Reading comprehension data was obtained through multiple choice test. Meanwhile, the data of critical reading was gained through the Essay Test. The results of this study revealed that: (1) there was an effect of Collaborative Strategic Reading on Students’ Reading Comprehension, (2) there was an effect of Critical Reading toward students’ reading comprehension, and (3) there were interactions between CSR and critical reading toward students’ reading comprehension. Keywords: Collaborative Strategic Reading (CSR), Critical Reading, Reading Comprehension